Modeling the Effect of Temperature on Membrane Response of Light Stimulation in Optogenetically-Targeted Neurons - Peixoto, Helton M.; Cruz, Rossana M. S.; Moulin, Thiago C.; Leão, Richardson N. (Frontiers in Computational Neuroscience, 2020)
Optogenetics is revolutionizing Neuroscience, but an often neglected effect of light stimulation of the brain is the generation of heat. In extreme cases, light-generated heat kills neurons, but mild temperature changes alter neuronal function. To date, most in vivo experiments rely on light stimulation of neural tissue using fiber-coupled lasers of various wavelengths. Brain tissue is irradiated with high light power that can be deleterious to neuronal function. Furthermore, absorbed light generates heat that can lead to permanent tissue damage and affect neuronal excitability. Thus, light alone can generate effects in neuronal function that are unrelated to the genuine “optogenetic effect.” In this work, we perform a theoretical analysis to investigate the effects of heat transfer in rodent brain tissue for standard optogenetic protocols. More precisely, we first use the Kubelka-Munk model for light propagation in brain tissue to observe the absorption phenomenon. Then, we model the optothermal effect considering the common laser wavelengths (473 and 593 nm) used in optogenetic experiments approaching the time/space numerical solution of Pennes' bio-heat equation with the Finite Element Method. Finally, we then modeled channelrhodopsin-2 in a single and spontaneous-firing neuron to explore the effect of heat in light stimulated neurons. We found that, at commonly used light intensities, laser radiation considerably increases the temperature in the surrounding tissue. This effect alters action potential size and shape and causes an increase in spontaneous firing frequency in a neuron model. However, the shortening of activation time constants generated by heat in the single firing neuron model produces action potential failures in response to light stimulation. We also found changes in the power spectrum density and a reduction in the time required for synchronization in an interneuron network model of gamma oscillations. Our findings indicate that light stimulation with intensities used in optogenetic experiments may affect neuronal function not only by direct excitation of light sensitive ion channels and/or pumps but also by generating heat. This approach serves as a guide to design optogenetic experiments that minimize the role of tissue heating in the experimental outcome.